Application of Motion Estimation Using Ultrasound Images - S., Ranjit; K. S., Sim; R., Besar; C. P., Tso (SPRINGER, 2008)
This paper presents a study on ultrasound imaging by using the hexagon-diamond search (HDS) method. The HDS algorithm is implemented on an ultrasound image to track object movement. The hexagon comprises seven points including the center point, with a smaller diamond covering four points inside the hexagon in order to finalize the focused search. The HDS algorithm extracts images into macro-blocks and performs the computation for image redundancy between frames. In addition, the HDS is able to determine the motion vector in the search region.